Beat the market: an investment adventure / Amir Hakim Osman, Ab. Razak Dahlan and Ahmad Zoolhelmi Alias - Osman, Amir Hakim; Dahlan, Ab. Razak; Alias, Ahmad Zoolhelmi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Beat the market is an investment game that allows the players to experience and enjoy the thrill and excitement of trading shares. Beat the market is not only just about having fun, it is also educational as the game was designed based on popular investment theories and also using realistic trading procedures which will help the players to strengthen their knowledge on basic investment strategies. At the end of the game, the players should be able to relate the investment theories and real-world investing and will make the players realise that in planning and monitoring investments, it requires more than just strong understanding of the theories. The ability to make quick and accurate responses is also essential in making good investment decisions. Beat the market will definitely be a hit to the educational industry whether as a learning tool on its own or being incorporated in a syllabus.